Glycosylation of luteolin in hydrophilic organic solvents and structure–antioxidant relationships of luteolin glycosides. Issue 28 (22nd June 2022) - Xu, Tingting; Wang, Chen; Jiang, Sijie; Yang, Tingting; Wu, Xueming
Abstract : Efficient glycosylation of luteolin in organic solvents and the structure–antioxidant relationships of luteolin glycosides were reported for the first time. Abstract : An effective approach was developed to biotransform luteolin glycosides in hydrophilic organic solvents. Bacillus cereus A46 cells showed high activity and stability in 5–20% (v/v) DMSO with 90–98% conversion rates of luteolin glycosides. Five glycosides of luteolin 7- O -β-glucoside, luteolin 4′- O -β-glucoside, luteolin 3′- O -β-glucoside, luteolin 7, 3′-di- O -β-glucoside and luteolin 7, 4′-di- O -β-glucoside were obtained. The addition of DMSO greatly promoted the solubility of luteolin and further regulated the formation of the main products from five luteolin glycosides to luteolin 7- O -β-glucoside (931.2 μM). Fourteen flavonoids and anthraquinones were used as tentative substrates. Glycosylation positions were located at the C-7, C-3′ or C4′ hydroxyl groups of flavonoids and C-5 hydroxyl group of anthraquinones. The 3′, 4′-dihydroxy arrangement played the key role for the antioxidant activity of luteolin.